Towards conceptually comprehensive and integrated theory of entrepreneurial opportunity - Oksanen, Matilda (My University, 2012)
Insufficient understanding of entrepreneurial opportunities characterizes entrepreneurship research (Companys & McMullen 2006, 302). Subsequently, the purpose of this study was to analyze the concept of entrepreneurial opportunity and to explore and synthetize the integrated theory of entrepreneurial opportunity. A theoretical and concept analytical approach was adapted. Findings of this study was that entrepreneurial opportunity concept was used for variety of different phenomena. No commonly accepted definition existed. Altogether 24 attributes that described the concept were found. The most frequently attached attributes were agent and action, new goods and services, market, value, new means ends or both, and future. Further, the results implied that opportunity could be best understood as a part of a process. Opportunity emerges out of intervened factors. Changes in the environment together with factors related to knowledge, cognition and social ties are the most important drivers of opportunity. Preventing factors that impeded the emergence of opportunity were typically related to cognitive and organizational factors. This study found a tendency towards more integrated theory of entrepreneurial opportunity. The integrated theory acknowledged the usefulness of both discovery and creation theories of opportunity in explaining opportunity. Yet three argument types of integrating two different opportunity theories were identified. These were process category, contextual category and complementing category. Opportunity is at the same time cognitive, social and linguistic construct, although it is shaped by the objective environment. Opportunity requires linguistic endeavors to become explicit. Materialization of opportunity occurs in a social context. Moreover, it is always characterized by some extent of subjectivity, as opportunities cannot appear without the agent and their action. Due to these the concept remains always to some extent ambiguous. Tolerating and harnessing change and investing in human and social capital create the preeminent environment for the entrepreneurial opportunity to be identified.